EFFECTS OF TRANSCRANIAL MAGNETIC STIMULATION ON KINDLED RATS AGGRESSIVE BEHAVIOR UNDER CONDITIONS OF DOPAMINERGIC SYSTEM FUNCTIONAL STATE MODULATION - Artyomenko, V. V.; Desyatsky, V. V. (Journal of Education, Health and Sport, 2015)
Artyomenko V. V., Desyatsky V. V. Вплив транскраніальної магнітної стимуляції на агресивну поведінку кіндлінгових щурів за умов модуляції стану дофамінергічної системи = Effects of transcranial magnetic stimulation on kindled rats aggressive behavior under conditions of dopaminergic system functional state modulation. Journal of Education, Health and Sport. 2015;5(12):64-72. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34949 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A64-72 http://pbn.nauka.gov.pl/works/676307 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 30.11.2015. УДК 616.853-092.9 ВПЛИВ ТРАНСКРАНІАЛЬНОЇ МАГНІТНОЇ СТИМУЛЯЦІЇ НА АГРЕСИВНУ ПОВЕДІНКУ КІНДЛІНГОВИХ ЩУРІВ ЗА УМОВ МОДУЛЯЦІЇ СТАНУ ДОФАМІНЕРГІЧНОЇ СИСТЕМИ EFFECTS OF TRANSCRANIAL MAGNETIC STIMULATION ON KINDLED RATS AGGRESSIVE BEHAVIOR UNDER CONDITIONS OF DOPAMINERGIC SYSTEM FUNCTIONAL STATE MODULATION В. В. Артьоменко, В. В. Десятський V. V. Artyomenko, V. V. Desyatsky Одеський національний медичний університет, Одеса Odessa National Medical University, Odessa Summary Kindling rats were observed to decrease the aggressive behavior threshold in the test of animals’ fights on the electrode floor. L-DOPA (100 mg/kg, i.p.) resulted in the rats’ aggressive behavior enhancement whereas haloperidol (0.5 mg/kg, i.p.) caused an aggressiveness increase. The increase of the aggressiveness threshold was also observed under the influence of a pulsed magnetic field (20 pulses). The combined influence of 10 of magnetic field pulses and L-DOPA (50,0 mg/kg, i.p.) which in case of their single administration failed to reveal any effect accompanied by a kindled rats aggressive behavior significant reduction. Aggressive behavior that occurs in conditions of chronic epilepsy syndrome suppressed under the influence of transcranial magnetic stimulation. This effect is realized due to the brain dopaminergic mechanisms activation. Ключові слова: transcranial magnetic stimulation, corazol, kindling, dopamine, haloperidol, aggressive behavior. Резюме У кіндлінгових щурів спостерігалось зниження порога розвитку агресивної поведінки в тестах бійок пар тварин на електродній підлозі. Під впливом L-DOPA (100 мг/кг, в/очер) спостерігалось підвищення порога агресивної поведінки щурів, в той час як галоперидол (0,5 мг/кг, в/очер) викликав підвищення агресивності. Також підвищення порога агресивності спостерігалось під впливом імпульсного магнітного поля (20 імпульсів). Поєднаний вплив 10 імпульсами магнітного поля і L- DOPA (50,0 мг/кг, в/очер), які при самостійному використанні не викликали ефекту, супроводжувалось зниженням виразності агресивної поведінки кіндлінгових щурів. Агресивна поведінка, яка виникає за умов виникнення хронічного епілептичного синдрому, гальмується під впливом транскраніальної магнітної стимуляції. Зареєстрований цей ефект реалізується завдяки активації дофамінергічних механізмів мозку. Ключові слова: транскраніальна магнітна стимуляція, коразол, кіндлінг, дофамін, галоперидол, агресивна поведінка. Резюме ВЛИЯНИЕ ТРАНСКРАНИАЛЬНОЙ МАГНИТНОЙ СТИМУЛЯЦИИ НА АГРЕССИВНОЕ ПОВЕДЕНИЕ КИНДЛИНГОВЫХ КРЫС ПРИ ИМЕНЕНИИ СОСТОЯНИЯ ДОФАМИНЕРГИЧЕСКОЙ РЕГУЛЯЦИИ. У киндлинговых крыс наблюдалось снижение порога развития агрессивного поведения в тестах драк пар животных электродном полу. Под влиянием L-DOPA (100 мг/кг, в/бр) наблюдалось повышение порога агрессивного поведения крыс, в то время как галоперидол (0,5 мг/кг, в/бр) вызывал повышение агрессивности. Повышение порога агрессивности наблюдалось также под влиянием импульсного магнитного поля (20 импульсов). Совместное воздействие 10 импульсами магнитного поля и L-DOPA (50,0 мг/кг, в/бр), которые при самостоятельном использовании не вызвали эффекта, сопровождалось снижением выраженности агрессивного поведения киндлинговых крыс. Агрессивное поведение, возникающее в условиях возникновения хронического эпилептического синдрома, угнетается под влиянием транскраниальной магнитной стимуляции. Отмеченный эффект реализуется благодаря активации дофаминергических механизмов мозга. Ключевые слова: транскраниальная магнитная стимуляция, коразол, киндлинг, дофамин, галоперидол.